SCN8A Encephalopathy with a Significant Long-Term Response to Lacosamide - Yokoyama, Azusa; Nakamura, Takuji; Ichinose, Fumio; Miya, Fuyuki; Kato, Mitsuhiro; Matsuo, Muneaki (Journal of Pediatric Neurology, 2024)
Developmental and epileptic encephalopathy associated with SCN8A variants (i.e., SCN8A encephalopathy) causes early-onset epilepsy, involuntary movements, hypotonia, and developmental delay. Sodium channel blockers are effective for treating SCN8A encephalopathy; however, the long-term effects are unknown. Herein, we report the long-term efficacy of lacosamide (LCM) treatment in a patient with SCN8A encephalopathy. Our patient, a 7-year-old girl, presented with a hyperekplexia-like excessive startle response, drug-resistant epilepsy with sinus arrest, and prolonged respiratory failure during the neonatal period. The patient was diagnosed with SCN8A encephalopathy caused by a de novo pathogenic variant of SCN8A: c.3979A > G; p.Ile1327Val. The patient experienced tonic clustered seizures daily, with dramatic responses to high doses of LCM, lasting approximately 3 years.
Keywords: SCN8A encephalopathy; hyperekplexia; sodium channel blocker; lacosamide